Neural implementation of musical expertise and cognitive transfers: could they be promising in the framework of normal cognitive aging? - FAUVEL, Baptiste; Groussard, Mathilde; Eustache, Francis; Desgranges, Béatrice; Platel, Hervé (Frontiers in Human Neuroscience, 2013)
Brain plasticity allows the central nervous system of a given organism to cope with environmental demands. Therefore, the quality of mental processes relies partly on the interaction between the brain’s physiological maturation and individual daily experiences. In this review, we focus on the neural implementation of musical expertise at both an anatomical and a functional level. We then discuss how this neural implementation can explain transfers from musical learning to a broad range of nonmusical cognitive functions, including language, especially during child development. Finally, given that brain plasticity is still present in aging, we gather arguments to propose that musical practice could be a good environmental enrichment to promote cerebral and cognitive reserves, thereby reducing the deleterious effect of aging on cognitive functions.